-9(x+5)=3(x-27)

Simple and best practice solution for -9(x+5)=3(x-27) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -9(x+5)=3(x-27) equation:


Simplifying
-9(x + 5) = 3(x + -27)

Reorder the terms:
-9(5 + x) = 3(x + -27)
(5 * -9 + x * -9) = 3(x + -27)
(-45 + -9x) = 3(x + -27)

Reorder the terms:
-45 + -9x = 3(-27 + x)
-45 + -9x = (-27 * 3 + x * 3)
-45 + -9x = (-81 + 3x)

Solving
-45 + -9x = -81 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
-45 + -9x + -3x = -81 + 3x + -3x

Combine like terms: -9x + -3x = -12x
-45 + -12x = -81 + 3x + -3x

Combine like terms: 3x + -3x = 0
-45 + -12x = -81 + 0
-45 + -12x = -81

Add '45' to each side of the equation.
-45 + 45 + -12x = -81 + 45

Combine like terms: -45 + 45 = 0
0 + -12x = -81 + 45
-12x = -81 + 45

Combine like terms: -81 + 45 = -36
-12x = -36

Divide each side by '-12'.
x = 3

Simplifying
x = 3

See similar equations:

| -15+5z+1z-9=0 | | 3a+2b=9 | | 8s+7s+2s-4= | | -4+4(1+4M)=-128 | | z+1= | | 6x^2-48x+96=0 | | P=10t-300 | | 12-2(4x-6)=8 | | -4.3=0.5n | | 4x^2-56x+180=0 | | (2x-3)(-2(3x+2))=y | | 3m+5m+6m-6= | | 3-9x=-6 | | 6x-5x+3x-9x= | | 20+2x+48-4x=34 | | 20(10)+2x+48-4x=34 | | 2x^2-5x-40=-3x | | 3x-5=12-32 | | -6-14+s=11s | | 3x-8+7x=2(5x-4) | | 6-2a=3a-9 | | 8x+4y=70 | | 2(1c-3)+12=5c-2c | | B=q+qwf | | 3x-5=2x-1 | | 4x^2+10x+16=0 | | 2(e-3)=5 | | 8b+3=10b-2(b-2)+3 | | 1(6x+7)=3*5 | | 6x+15-2x=0 | | 3a+2=32 | | 12x-4y+10=0 |

Equations solver categories